SISTEM INFORMASI PENJUALAN PARFUM ONLINEPADA TOKO DUTA ANALISA PARFUM BERBASIS WEB - Denada Fatimah Zahra; HM. John Dien; Wasiah Magfiroh (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Toko Duta Analisa Perfume is a shop that sells various types of perfumes and bottles. The lack of optimal publication to the public has resulted in this shop not being well known by the wider community so that the sales target is not optimal. This website was built using the PHP programming language with a database using MySql. The processes that occur in this website are the registration process, ordering and payment process. The data collection method used is by way of interviews and observation. The research method used is descriptive analysis method, namely research that is intended to collect data that can provide a clearer picture of an object of research and then an analysis of the object of research is carried out. The software analysis model used is structured analysis modeling. The tools used are flowmap, ERD (Entity Relationship Diagram) and to describe the process used is DFD (Data Flow Diagram). The advantage of using this application is that it makes it easier for sellers in a very efficient time and for buyers it makes it easy to choose goods and make payment transactions just at home.